Peningkatan Kepercayaan Diri Siswa melalui Video-Based Learning dalam Pembelajaran Tari Berbasis Budaya di Sekolah Dasar - Veradiana Novitasari (Journal of Education Research, 2026)
This study aims to analyze the influence of Video-Based Learning (VBL) in culture-based dance learning on increasing the confidence of elementary school students. The study used a quasi-experimental design with a pretest-posttest control group design approach. The research subjects amounted to 25 students who were given learning treatment using VBL. The research instruments included confidence questionnaires, observation sheets, and learning documentation. Data analysis was carried out using descriptive statistics and paired sample t-test to determine the difference before and after treatment. The results showed an increase in the average confidence score from 39.72 in the pretest to 66.40 in the posttest. Statistical tests showed a significant difference with a significance value of 0.000 (p < 0.05). In addition, the results of observation and documentation show an increase in active participation and students' courage in expressing themselves during learning. These findings show that the application of VBL in culture-based dance learning has a significant influence on increasing student confidence. Thus, VBL can be an alternative effective learning strategy in developing the affective aspects of students in elementary school